The pneumococcal two-component system SirRH is linked to enhanced intracellular survival of Streptococcus pneumoniae in influenza-infected pulmonary cells - Reinoso Vizcaíno, Nicolás Martín (2020)
The virus-bacterial synergism implicated in secondary bacterial infections caused by Streptococcus pneumoniae following infection with epidemic or pandemic influenza A virus (IAV) is well documented. However, the molecular mechanisms behind such synergism remain largely ill-defined. In pneumocytes infected with influenza A virus, subsequent infection with S. pneumoniae leads to enhanced pneumococcal intracellular survival. The pneumococcal two-component system SirRH appears essential for such enhanced survival. Through comparative transcriptomic analysis between the ΔsirR and wt strains, a list of 179 differentially expressed genes was defined. Among those, the clpL protein chaperone gene and the psaB Mn+2 transporter gene, which are involved in the stress response, are important in enhancing S. pneumoniae survival in influenza-infected cells. The ΔsirR, ΔclpL and ΔpsaB deletion mutants display increased susceptibility to acidic and oxidative stress and no enhancement of intracellular survival in IAV-infected pneumocyte cells. These results suggest that the SirRH two-component system senses IAV-induced stress conditions and controls adaptive responses that allow survival of S. pneumoniae in IAV-infected pneumocytes.